Racial Inequality in Democratic Accountability: Evidence from Retrospective Voting in Local Elections. Issue 3 (23rd December 2016) - Flavin, Patrick; Hartney, Michael T.
Abstract: One important and, to date, overlooked component of democratic accountability is the extent to which it might exacerbate existing societal inequalities if the outcomes for some groups of citizens are prioritized over others when voters evaluate governmental performance. We analyze a decade of California school board elections and find evidence that voters reward or punish incumbent board members based on the achievement of white students in their district, whereas outcomes for African American and Hispanic students receive comparatively little attention. We then examine public opinion data on the racial education achievement gap and report results from an original list experiment of California school board members that finds approximately 40% of incumbents detect no electoral pressure to address poor academic outcomes among racial minority students. We conclude by discussing the implications of these findings for several scholarly literatures, including retrospective voting, racial inequality in political influence, intergovernmental policymaking, and education politics .